Does Spot Nifty Fluctuate with Macroeconomic Indicators? - Ahalawat , Shweta; Patro , Archana (Asian Journal of Empirical Research, 2019)
The major goal of this research is to examine the relationship between Spot Nifty (the current price of Nifty which comprises fifty shares acquainted by the national stock exchange of India) and selected macroeconomic variables such as the exchange rate of four countries, interest rate, and Foreign Institutional Investors, which immensely affect the execution of the financial market with reference to the Indian financial market. Data from the 15 years from 2003 to 2018 have been used to determine the clear picture of pre- and post-crisis 2008. The ADF test has been applied to test the stationary of the data. The research found a noteworthy interrelation which implies that there is a positive association between certain macroeconomic factors and spot Nifty.